2003
DOI: 10.1097/00024382-200302000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma Cruzi Sensitizes Mice to Fulminant Seb-Induced Shock: Overrelease of Inflammatory Cytokines and Independence of Chagas' Disease or TCR V??-Usage

Abstract: Trypanosoma cruzi-infected mice display increased susceptibility to shock induced by injection of lipopolysaccharide (LPS), anti-CD3, or resulting from interleukin (IL)-10-defective response to the parasite itself, but the basis of such susceptibility remains unknown. Herein, we tested the susceptibility of mice inoculated with virulent and avirulent T. cruzi to staphylococcal enterotoxins (SE), potent inducers of inflammatory cytokine secretion. Mice infected with T. cruzi CL-strain or inoculated with the avi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Swiss mice infected with the Y strain of T. cruzi usually die on May 9, 2018 by guest http://aac.asm.org/ between 18 and 21 days postinfection, as a result of a complex host-parasite interplay involving inflammation, systemic activation of the natural and acquired immune responses, progressive renal and heart dysfunctions, and eventually systemic shock (20). We found that pharmacological treatment of T. cruzi-infected mice with a single dose of 10 mg/kg SB-431542 given on day 3 postinfection led to improved survival rates compared to untreated animals and that this difference was significant at 20 dpi.…”
Section: Discussionmentioning
confidence: 99%
“…Swiss mice infected with the Y strain of T. cruzi usually die on May 9, 2018 by guest http://aac.asm.org/ between 18 and 21 days postinfection, as a result of a complex host-parasite interplay involving inflammation, systemic activation of the natural and acquired immune responses, progressive renal and heart dysfunctions, and eventually systemic shock (20). We found that pharmacological treatment of T. cruzi-infected mice with a single dose of 10 mg/kg SB-431542 given on day 3 postinfection led to improved survival rates compared to untreated animals and that this difference was significant at 20 dpi.…”
Section: Discussionmentioning
confidence: 99%
“…The immune response of T cells to SEB displays a biphasic change [5, 6] which consists of an early activation presented as T cell proliferation and a second anergy due to apoptosis of the appropriate T cells. Ultimately, the hyper-response and immunosuppression of T cells following SEB exposure may lead to illness and disease in mammals [7, 8]. A variety of literatures [912] have demonstrated the influence of SEB exposure on T cells during adulthood or neonatal period in animal experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Mice have historically been used by various groups as an alternative to monkeys for studying superantigen-mediated effects in vivo 79 - 88 . From a cost perspective, mice are very feasible for basic toxin studies and discovery of therapeutics/vaccines for combating staphylococcal superantigen-induced shock.…”
Section: In Vivo Effects: Animal Models and Morementioning
confidence: 99%
“…Additionally, mice are naturally less susceptible (vs. monkeys) to SEs and TSST-1 because of decreased affinity for MHC II 81 , 84 . Therefore, potentiating agents such as d -galactosamine, actinomycin D, lipopolysaccharide (LPS), viruses, or even protozoa are used by various groups with different mouse strains 80 - 83 , 87 , 88 . These agents amplify SE or TSST-1 effects in mice so that practical, lower amounts of these protein toxins elicit a quantifiable form of toxic shock (i.e., lethality or temperature change) useful for therapeutic and vaccine discovery.…”
Section: In Vivo Effects: Animal Models and Morementioning
confidence: 99%